The variability of serological and molecular diagnosis of feline immunodeficiency virus infection - Bienzle, D. (Canadian Veterinary Medical Association, 2004)
Diagnosis of feline immunodeficiency virus (FIV) infection by polymerase chain reaction (PCR) has recently become available, but little is known about the performance of this assay. The purpose of this study was to determine the sensitivity and specificity of PCR diagnosis of FIV infection. Replicate aliquots of blood samples from cats identified as FIV positive or negative by 2 previous enzyme-linked immunosorbent assay (ELISA) results, and from clinically healthy dogs, were submitted to different laboratories for FIV serologic diagnosis and PCR. The PCR products obtained in 1 laboratory were sequenced to determine the FIV subtype. The PCR assays correctly identified 100%, 80%, and 50% of the FIV-positive samples, and 100%, 90%, and 70% of FIV-negative samples. Each dog sample was reported as FIV PCR positive at least once, and FIV subtypes A, B, and C were identified. It was concluded that PCR tests currently available for FIV infection are unreliable, with highly variable sensitivity and specificity.